Fetal Femur Length and Abdominal Circumference Ratio in Bangladesh - Rashid, Sabrina Q (Bangladesh Journal of Obstetrics & Gynaecology, 2011)
Objective: The ratio of fetal femur length and abdominal circumference is one of the important ratios. But we do not have any study on it in our country so far. Therefore a study was conducted to prepare a table based on Bangladeshi population. Method: Well dated pregnancies were included in a cross-sectional prospective study. By fitting Polynomial regression model a table and a graph were prepared. Nomograms of Caucasian population which were established before, were compared with this study. Results: A chart of the raw data of 1223 subjects with superimposed fitted percentiles was produced. The quadratic model showed a good fit to the data. 3rd, 10th, 50th, 90th and 97th percentiles, means and two standard deviations of the data were derived. Conclusion: These table and charts can be useful for accurate assessment of fetal femur length/abdominal circumference ratio to detect the type of fetal growth abnormality, symmetrical or asymmetrical. This study shows that there is similarity of this ratio with the western ratio unlike the individual fetal parameters. Key words: Femur length/abdominal circumference ratio; Bangladesh. Bangladesh J Obstet Gynaecol, 2009; Vol. 24(2) : 52-55 DOI: http://dx.doi.org/10.3329/bjog.v24i2.8528